2013
DOI: 10.1097/meg.0b013e32835c9f69
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance

Abstract: In CHC-4 patients, IR is highly prevalent and independently associated with age, obesity, SF, and severe steatosis. Management of IR might significantly improve the prognosis of CHC-4 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In another study of chronic HCV patients [ 56 ], obese patients had a greater risk of advanced fibrosis. Similar results were found by El-Ray et al in Egypt [ 55 ]. The harmful effects of obesity are caused by a state of chronic metabolic inflammation induced in the liver, which may predispose individuals to liver fibrosis and non-alcoholic fatty liver disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In another study of chronic HCV patients [ 56 ], obese patients had a greater risk of advanced fibrosis. Similar results were found by El-Ray et al in Egypt [ 55 ]. The harmful effects of obesity are caused by a state of chronic metabolic inflammation induced in the liver, which may predispose individuals to liver fibrosis and non-alcoholic fatty liver disease.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, patients’ body mass index was significantly associated with the risk of liver fibrosis, as obese HIV-HCV co-infected patients were six times more likely to have ALF. Several studies have shown a strong association between obesity and disease progression in chronic HCV patients [ 54 , 55 , 56 , 57 ]. In a study of an American cohort of chronic HCV patients with available liver biopsies, Younossi et al [ 57 ] highlighted that overweight and obese patients were much more likely to have advanced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among their findings, the onset of liver fibrosis ranged between 5 to 15.2 years. While one systematic review of 57 articles estimated that cirrhosis onset after 20 years of chronic HCV infection was 22% for the liver clinic series [77]. Therefore, it seems that HIV/HCV coinfection would shorten the onset of cirrhosis development.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a significant risk factor for advanced fibrosis in patients with NAFLD [ 29 ]. Insulin resistance is also a major factor associated with NAFLD and significant liver fibrosis [ 30 , 31 ]. NAFLD itself was a multisystem disease and associated with factors that mediate interindividual variations in the development of extrahepatic manifestations including type 2 diabetes mellitus [ 32 ].…”
Section: Discussionmentioning
confidence: 99%